PENGARUH LATIHAN DRILL SMASH TERHADAP HASIL KETERAMPILAN SMASH PADA TIM BOLA VOLI PUTRA SMPN 1 PEKANBARU - Elvagen, M. Aurelio; Juita, Ardiah; S, Wedi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2025)
Abstract: The purpose of this study was to determine the Effect of Smash Drill Training on Volleyball Smash Skills in the Men's Football Team of SMP Negeri 1 Pekanbaru. This study is an experimental research type. It was carried out on the Volleyball field of SMP Negeri 1 Pekanbaru on Jalan St. Syarif, Rintis, Lima Puluh Kota District, Pekanbaru, on Tuesday, May 28, 2025, to July 29, 2025. The data collection method in this study was carried out two tests, namely the initial test (pre test) before performing the attack/smash stroke and the final test (post-test), after performing the attack/smash stroke practice for 16 meetings three times a week. The sample consisted of 12 people. Based on the t-test analysis, it produces a t-count of 5.333 and a T-table of 1.363. This means that t-count>t-table. And based on statistical data analysis, there is a pre-test average of 22.08 and a post-test average of 46.42. Based on the t-test after calculating the basis, there is a difference in numbers that increase or increase by 24.34. It can be concluded that the athlete's ability is influenced by the Smash Drill Training needed to support the frequency when doing training in improving Smash skills. Based on the findings and data processing above, it can be concluded as follows: There is a significant influence of smash drill exercises (x) on smash skills in the men's volleyball team of SMPN 1 Pekanbaru. Based on the researcher's view of Smash Drill Training, it can reap maximum results because of the habits carried out by each individual athlete. Key Words: Smash Drill Practice, Smash Skills